A solution for the inner area of CBM-TOF with pad-MRPC - Wang, Yifei; Herrmann, Norbert; Deppner, Ingo Martin; Loizeau, Pierre-Alain; Simon, Christian (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2017)
The Compressed Baryonic Matter (CBM) experiment has decided to use the Multi-gap Resistive Plate Chambers(MRPC) technology to build its Time-Of-Flight (TOF) wall. CBM-TOF requires a rate capability over 20kHz/cm2 for inner region. A 10-gap pad-MRPC assembled with low resistive glass is designed to construct this area. The prototypes, which consist of 10×0.22mm gas gaps and 2×8 20mm×20mm readout pads, require fewer electronic channels compared to the strip design. A timing resolution of around 60ps and an efficiency above 98% were obtained in a cosmic test and a beam test taken in 2014 October GSI beam time. The results show that the real-size prototypes fulfill the requirements of the CBM-TOF.
Available online 30 June 2016
Gesehen am 26.11.2018